217k views
5 votes
How to solve (with steps)
3 ( x + 2 ) = 9 ( 6 - x )

User Tachy
by
4.7k points

2 Answers

3 votes

Answer:

x=4

Explanation:

3 (x+2) = 9 (6-x)

3x + 6 = 54 - 9x

-6 = -6

3x = 48 - 9x

+9x +9x

12x = 48

/12 /12

x = 4

User LaurentG
by
5.3k points
5 votes

Answer: x = 4

Explanation:

Distribute the 3 and the 9


3(x+2)=9(6-x)\\3x+6=54-9x

Add 9x to both sides


12x+6=54

Subtract 6 on both sides and simplify


12x = 48\\x=4

User Miracle
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.